1988
DOI: 10.1080/03015521.1988.10425647
|View full text |Cite
|
Sign up to set email alerts
|

Selection of fungal antagonists for biological control of onion white rot in New Zealand

Abstract: Six fungal species were selected from a total of 76 on the basis of their antagonism to the onion white rot pathogen, Sclerotium cepivorum, in dual culture. Gliocladium roseum, G. virens, Trichoderma viride and Coniothyrium minitans exhibited their antagonism by competing successfully with the pathogen for space and nutrients whilst Chaetomium globosum and Penicillium expansum released antibiotic substances into the agar medium which inhibited the growth of S. cepivorum at a distance. Four of the six test fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
(16 reference statements)
2
25
0
Order By: Relevance
“…It agrees with an earlier observation by Fawzy (1982) that reduced growth of S. sclerotiorum and Sclerotium cepivorum occurred following incorporatio n of culture ® ltrates of C. minitans into liquid media. However, in New Zealand, culture ® ltrates of C. minitans grown on molasses± yeast medium incorporate d back into PDA following ® lter sterilization had no eVect on radial growth of S. cepivorum even though some inhibitio n of hyphal growth of S. cepivorum by C. minitans had been detected in agar confrontationa l tests (Harrison & Stewart, 1988). This may re¯ect diVerent isolates of C. minitans and experimental conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It agrees with an earlier observation by Fawzy (1982) that reduced growth of S. sclerotiorum and Sclerotium cepivorum occurred following incorporatio n of culture ® ltrates of C. minitans into liquid media. However, in New Zealand, culture ® ltrates of C. minitans grown on molasses± yeast medium incorporate d back into PDA following ® lter sterilization had no eVect on radial growth of S. cepivorum even though some inhibitio n of hyphal growth of S. cepivorum by C. minitans had been detected in agar confrontationa l tests (Harrison & Stewart, 1988). This may re¯ect diVerent isolates of C. minitans and experimental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…However, biomass production in these complex systems is diYcult to measure (Ooijkaas et al, 1998a) and no attention has been paid to the production of antifunga l metabolites. Indeed, consistent evidence for the production of antifunga l metabolites by C. minitans is poor (Fawzy, 1982;Harrison & Stewart, 1988;Whipps & Gerlagh, 1992).…”
Section: Introductionmentioning
confidence: 96%
“…73, No. 4: 327-330, 2004 329 ACTA SOCIETATIS BOTANICORUM POLONIAE regard to production of these metabolites was found by Dennis and Webster (1971); Harrison and Stewart (1988) and Rudawska et al (1993). Moreover, mycoparasitism of T. harzianum on rhizomorphs of A. gallica was reported by Dumas and Boyonoski (1992).…”
Section: Discussionmentioning
confidence: 77%
“…and Zygorrhynchus moelleri Vuill. (Pentland 1965;Kelly 1976;Harrison and Stewart 1988;Anselmi et al 1992;Fox et al 1994;Gallet and Lung-Escarmant 1994;Kwana and £akomy 1998;Languasco et al 2001). To our knowledge there is very little information available in the literature on the effect of inorganic compounds in pathogen-microorganism interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Kleifeld & Chet (1992) demonstrated the presence of Trichoderma inside the root cortex of treated plants, suggesting a mycorrhizal-like relationship and induced resistance effects to explain plant-growth promotion by the fungus. Moreover, it has been reported that failure of fungal species as seed coating may have resulted from suppression of those fungi by exudates from the roots (Harrison & Stewart, 1998;Kay & Stewart, 1994). Similarly, fungal isolates used here could be affected in this way and this may account in part for the no disease control afforded by the fungi when applied as a seed coating.…”
Section: Discussionmentioning
confidence: 90%